Determination of the diameter of simulated human capillaries using shifted position‐diffuse reflectance imaging - Späth, Moritz; Hohmann, Martin; Rohde, Maximilian; Lengenfelder, Benjamin; Stelzle, Florian; Klämpfl, Florian (Journal of Biophotonics, 2021)
Multiple diseases are associated with a wide spectrum of microvascular dysfunctions, microangiopathies and microcirculation disorders. Monitoring the microcirculation could thus be useful to diagnose many local and systemic circulatory disorders and to supervise critically ill patients. Many of the scores currently available to help identify the condition of a microcirculation disorder are invasive or leave scope for interpretation. Thus, the present study aims to investigate with Monte‐Carlo simulations (as numerical solutions of the radiative transfer equation) whether shifted position‐diffuse reflectance imaging (SP‐DRI), a non‐invasive diagnostic technique, reveals information on the capillary diameter to assess the state of the microcirculation. To quantify the SP‐DRI signal, the modulation parameter K is introduced. It proves to correlate almost perfectly with the capillary diameter (urn:x-wiley:1864063X:media:jbio202000465:jbio202000465-math-0001), making it a valid parameter for reliably assessing microcirculation. SP‐DRI is emerging as an important milestone on the way to early and conveniently diagnosing microcirculation associated diseases.<br
Keywords: shifted position‐diffuse reflectance imaging; microcirculation; critically ill patients; modulation parameter; turbid media; human capillary; Monte‐Carlo simulation